Research on structure design and flow field characteristics of the novel jet bit for radial horizontal drilling. Issue 5 (15th August 2018) - Bi, Gang; Li, Mengmeng; Dou, Liangbin; Qu, Zhan
Abstract: The self‐propelled swirling jet bit was designed to ensure the rock‐breaking efficiency of radial horizontal drilling and meet the roundness of borehole diameter and borehole shape. The jet bit provides swirling jet through internal rotating impellers and increases the drilling depth by jetting through the central holes on the impeller. Based on numerical simulation method, RNG k−ε turbulence model was employed to analyze the three‐dimensional flow characteristics of flow field inside and outside of the two kinds of jet bits. Moreover, the rock‐breaking efficiency of the two jet bits was also compared and analyzed in accordance with the laboratory experiments. The results show that the simulated bottom‐hole flow field for the two jet bits can be both divided into bottom‐hole overflow area, forward jetting area, and backward jetting area. The forward jet is a jet beam which consists of a central jet and four circumferentially equispaced jets, which generates more complex overflow area at the bottom hole. The maximum jet speed and the jet impact energy of forward jetting from the combined swirling and round multijet bit are larger than that of the swirling multijet bit. The speed attenuation law of forward jet nozzle from the two kinds of jet bits is similar. They both increase slowly in the mixing zone, while increase remarkably when approach to the nozzle. Then decrease linearly in the impact zone, and decline straightly when get close to the impact area. The simulation results of flow field characteristics are in coincidence with the actual rock‐drilling features. Therefore, the simulation results of flow field characteristics can provide guidance for jet bit design and structure parameter optimization for radial horizontal drilling. Abstract : The radial horizontal drilling is a significant technology in exploration of low‐permeability and coal‐bed gas reservoir. The self‐propelled swirling jet bit was designed to ensure the rock‐breaking efficiency of radial horizontal drilling and meet the roundness of borehole diameter and borehole shape.